Saklar Lampu Otomatis dengan Kendali Kendali Android Berbasis Mikrokontroller: Array - Irawan, Amri; Hasibuan, Ade; Sembiring, Arnes (Universitas Harapan Medan, 2021)
Like in a room or classroom having a light switch for manual control, sometimes it's lazy to move or forget to turn it on and off, resulting in a waste of electricity. By utilizing technology and developing humans can create a technology that makes activities more efficient. This tool is designed to turn the lights on and off automatically and also control manually withcontrol smartphone, for example automatic control, at 06.30 Arduino will give commands to the servo motor to turn off the lights and at 18.00 the Arduino will turn on the lights, thencontrol manual is Android controls. Previously requiring an application on a smartphone , first designed the application using the MIT APP INVENTOR then transferred to Android.